The impact of the users’ seek values on consumer intention to use SST in multiple service industries in Saudi Arabia - Alotaibi, Badah Homuod; Al-Matari, Ebrahim Mohammed (Canadian Center of Science and Education, 2015)
This study investigated the effect of users’ seek values on consumer intention to use SST in multiple service industries in Saudi Arabia.The sample consists of 400 sample units where data is gathered with the help of a questionnaire.The study employed regression analysis to examine the independent variables-dependent variables relationship.Moreover, the outcome of the study revealed that a positive and significant association is present between user’s seek values and consumer intention to use SST.The research provides limitations and suggestions for future research before the study is concluded.